(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Poor learning attitude of undergraduate students makes them less confident in applying public health principles later in life as a professional. To address this problem, perceptions of the learners, at the receiving end of the curriculum, were taken to improve current teaching curriculum in community medicine. Objectives : To identify the perceptions and expectations of learners towards Community Medicine curriculum and to compare these with the existing curriculum. Materials and Methods: A cross sectional study was conducted by administering self-filled semi-structured questionnaire to the third MBBS phase I students. Majority of the questions were open ended to elicit students’ responses in their own words. Performa contained questions like preferred method of teaching various topics, reasons for preferring particular method, desired changes in curriculum and examination pattern etc. Results: One third of the students (33.6%) reported they were not satisfied with current teaching methodology. Least interesting method of teaching reported by students was lecture (51.5%). Reasons were- less interesting, no interaction with students, long monotonous presentations etc. One fourth of the students (25.74%) wanted more interactive methods of teaching in the form of group discussions, role play etc. Changes needed in curriculum were- modification in timing of teaching biostatistics and internal examination (from second to third year), inclusion of MCQs in lectures and examinations, more frequent examinations in third, revision classes after syllabus completion etc. Conclusion: Satisfaction of the students is poor with current teaching pattern and they expect more interactive methods of teaching along with increased faculty-student interaction.